2011
DOI: 10.1017/s0007114511001589
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed extract supplementation prevents high-fructose diet-induced insulin resistance in rats by improving insulin and adiponectin signalling pathways

Abstract: Recent evidence strongly supports the contention that grape seed extract (GSE) improves hyperglycaemia and hyperinsulinaemia in highfructose-fed rats. To explore the underlying molecular mechanisms of action, we examined the effects of GSE on the expression of muscle proteins related to the insulin signalling pathway and of mRNA for genes involved in the adiponectin signalling pathway. Compared with rats fed on a normal diet, high-fructose-fed rats developed pathological changes, including insulin resistance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 44 publications
3
31
0
Order By: Relevance
“…Stull et al, 2010 reported increased insulin sensitivity in obese, non-diabetic, and insulinresistant subjects after 8 weeks blueberry supplementation using the hyperinsulinemic euglycemic clamp procedure [16] and Brasnyó et al showed that resveratrol, a stilbene polyphenol found in red wine, improved insulin sensitivity in human subjects with type II diabetes [33]. Taken collectively, the results of the current study along with the findings from animal studies [18,19] suggests that GSE could improve insulin resistance. However, future studies using conventional insulin clamp procedures are required to confirm this effect [16].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Stull et al, 2010 reported increased insulin sensitivity in obese, non-diabetic, and insulinresistant subjects after 8 weeks blueberry supplementation using the hyperinsulinemic euglycemic clamp procedure [16] and Brasnyó et al showed that resveratrol, a stilbene polyphenol found in red wine, improved insulin sensitivity in human subjects with type II diabetes [33]. Taken collectively, the results of the current study along with the findings from animal studies [18,19] suggests that GSE could improve insulin resistance. However, future studies using conventional insulin clamp procedures are required to confirm this effect [16].…”
Section: Discussionsupporting
confidence: 69%
“…These effects have also been associated with improvements in insulin sensitivity [16] and postprandial insulin responses [9]. Grape seeds are a concentrated source of polyphenols and have received considerable attention for their antioxidant capacity and biological effects after chronic consumption [17][18][19][20]. In the present study, we tested the hypothesis that acute supplementation with grape seed extract (GSE) would attenuate meal-induced alterations in the oxidant and inflammatory status in men and women with the MetS.…”
mentioning
confidence: 97%
“…Both GSE treatments significantly increased plasma adiponectin levels and reduced plasma TAG levels compared to the highfructose control group. Furthermore, a high-fructose diet supplemented with 1% GSE significantly inhibited suppression of GLUT-4 protein expression and increased glycogen accumulation in skeletal muscle compared to the high-fructose control group and both GSE treatments significantly restored mRNA expression of adiponectin levels compared to the positive control 74 . Chronic HF and high-fructose diets can reduce tissues responsiveness to insulin and impair glucose metabolism by down-regulating the expression of insulin-stimulated 22 proteins and mRNA genes involved in insulin signaling.…”
mentioning
confidence: 88%
“…The adverse effects of the well-known cytokine TNF-α have been extensively studied and will be described in detail later in this review. Expression of the adipocyte-specific protein adiponectin, helps to modulate FFA catabolism via stimulation of various nuclear receptors thus contributing to lower levels of circulating FFA and glucose 72,74 .…”
mentioning
confidence: 99%
See 1 more Smart Citation